BUILDING EFFECTIVE LEADERSHIP AT MIN I BANDUNG: A COMBINATION OF TRANSFORMATIONAL AND TRANSACTIONAL STYLES - Indah Rosiana; Mulyawan Safwandy Nugraha (Program Studi Manajemen Pendidikan Islam, 2026)
Leadership plays an important role in determining the direction and quality of education. At MIN 1 Bandung, the effectiveness of the principal’s leadership is a key factor in building a professional, disciplined, and value-oriented work culture based on Islamic principles. This study aims to describe how the combination of transformational and transactional leadership styles can create an effective leadership pattern within the school environment. The research employed a qualitative approach using a case study method through interviews, observations, and document analysis. The findings reveal that transformational leadership fosters work motivation, builds a shared vision, and creates a collaborative working atmosphere. Meanwhile, transactional leadership supports the establishment of discipline, responsibility, and a clear system of rewards and sanctions. The combination of both styles results in balanced leadership between motivation and control, proving effective in improving teachers’ performance and the overall quality of education at MIN 1 Bandung. These findings emphasize that the integration of transformational and transactional leadership can serve as a strategic model for strengthening educational leadership in schools